EFFECTIVENESS OF THE REHABILITATION APPROACH BASED ON THE VISUAL MODEL OF MOBIUS TAPE IN THE TREATMENT OF MYOFASCIAL PAIN SYNDROME OF THE CERVICAL REGION IN COMBATANTS - Ye. Yu. Strashko (Проблеми екології та медицини)
During combat activities, the consequences of contusive and traumatic injuries to the spine, which lead to myofascial pain, in particular in the neck area, are of great importance. Myofascial pain syndrome, localized in the muscles and fascia, can range from mild discomfort to excruciating pain. To optimize personal rehabilitation programs in health care practice, for additional visualization of educational and practical activities, it was suggested to consider the rehabilitation process as a "motor and mental dialogue" at the same time, and also to use a topological object - the Möbius strip as a visual, multi-vector, interdisciplinary, plastic model of rehabilitation. The paper focuses on the study of the effectiveness of using the ecological approach in rehabilitation practice. The research was conducted on the basis of the Municipal Enterprise "Poltava Regional Clinical Hospital for War Veterans" of Poltava Regional Council. 42 military servicemen - participants of combat activities with a diagnosis of the myofascial pain syndrome of the cervical area were included in the study. As a component of the ecological approach, an individually developed program of comprehensive rehabilitation intervention aimed at the biomechanically interconnected muscle spirals, the diaphragm and masticatory muscles, and the temporomandibular joint was used. The method of active rehabilitation in patients using a program of comprehensive rehabilitation intervention for biomechanically interconnected muscle spirals, diaphragm and masticatory muscles, and temporomandibular joint, was based on a course of training with a multidisciplinary rehabilitation team lasting 21 days - 3 - 5 sessions with the doctor every day and 6-8 sessions according to the video sample recorded by the doctor. A statistically significant decrease in the intensity of pain according to VAS and an increase in the angle of painless lateral movement with an element of rotation may indicate the effectiveness of rehabilitation measures already on the seventh day of treatment. A decrease in the intensity of pain and an increase in the angle of painless lateral movement with an element of rotation in the experimental group, as compared to the control group, may indicate the advantage of using the proposed program at the same time as standard approaches in rehabilitation. The model proposed in the study can act not only as a treatment and rehabilitation tool but also as a visual training tool for future specialists, which has several advantages over traditional models. In particular, it involves low cost and ease of implementation, and it should be noted that the comprehensive, at first glance, rehabilitation process is simplified due to mathematical logic, sequence, creativity, and game form.